Knowledge Graph Application in Education: a Literature Review - Rizun, Mariia (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
In modern and developing economic systems, Knowledge Management (KM) is considered to be one of the most important activities of almost any organization. KM process at universities includes didactic processes, among which we distinguish the process of individualization of education. Such process requires a large amount of information to be processed both by university workers and students. This paper suggests that Knowledge Graphs are a technology that facilitates and enhances KM processes at universities and gives an extended review of a Knowledge Graph phenomenon.